The evolution of Japan's "misplacement" : from Meiji restoration to the Post-Cold War era - Koga, Kei (2022)
This article argues that since the Meiji Restoration, the degree of Japan’s misplacement has changed, depending on its structural power and ability to shape the concept of ‘Asia’ as a region. More specifically, there are three historical turning points: first, from the Meiji Restoration to the Pacific War (hard misplacement); second, post-World War II to the end of the Cold War (soft misplacement); and third, post-Cold War to the present (relative well-placement). In each period, Japan was faced with a different concept of ‘Asia’ and attempted to modify its identity and roles accordingly. The degree of ’misplacement’ is thus not static, but elastic, and such a status is not a permanent attribute of the state. Changes occur when states undertake a role location process, particularly during or after a change in the regional environment.